Analysis of the S-locus structure in Prunus armeniaca L. Identification of S-haplotype specific S-RNase and F-box genes - Romero, Carlos; Vilanova, S.; Burgos, Lorenzo; Martínez-Calvo, José; Vicente, M.; Llácer, Gerardo; Badenes, María L. (2017)
The gametophytic self-incompatibility (GSI) system in Rosaceae has been proposed to be controlled by two genes located in the S-locusan S-RNase and a recently described pollen expressed S-haplotype specific F-box gene (SFB). However, in apricot (Prunus armeniaca L.) these genes had not been identified yet. We have sequenced 21kb in total of the S-locus region in 3 different apricot S-haplotypes. These fragments contain genes homologous to the S-RNase and F-box genes found in other Prunus species, preserving their basic gene structure features and defined amino acid domains. The physical distance between the F-boxand the S-RNase genes was determined exactly in the S 2-haplotype (2.9kb) and inferred approximately in the S 1-haplotype (< 49kb) confirming that these genes are linked. Sequence analysis of the 5′ flanking regions indicates the presence of a conserved region upstream of the putative TATA box in the S-RNase gene. The three identified S-RNase alleles (S 1, S 2 and S 4) had a high allelic sequence diversity (75.3 amino acid identity), and the apricot F-box allelic variants (SFB1, SFB2 and SFB4) were also highly haplotype-specific (79.4 amino acid identity). Organ specific-expression was also studied, revealing that S 1- and S 2-RNases are expressed in style tissues, but not in pollen or leaves. In contrast, SFB 1 and SFB 2 are only expressed in pollen, but not in styles or leaves. Taken together, these results support these genes as candidates for the pistil and pollen S-determinants of GSI in apricot.